The Influence of Social Media Marketing and Electronic Word of Mouth on Visit Intention to Kura Kura Boneoge Beach Club - Andi Muhammad Fikri; Sutomo, Maskuri; Nuriya Santi, Ira; Zeylo Auriza, Mohammad (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to analyze the influence of social media marketing and electronic word of mouth on interest in visiting Kura Kura Boneoge Beach Club. The study used a quantitative approach with 105 respondents and was analyzed using multiple linear regression. The results showed that both variables had a positive and significant effect with an Adjusted R² of 0.725. Social media marketing had a more dominant influence than electronic word of mouth. These findings indicate that social media marketing and electronic word of mouth play an important role in increasing tourist interest in visiting.